Introduction - Imagined laboratories: Colonial and national racialisations in Island Southeast Asia - Anderson, Warwick (2018)
The nature of human difference in Southeast Asia continues to excite scientific research and speculation, as it has for centuries. Only now scientists are more likely to describe humanity in the region in terms of population genetics than rigid racial typologies. They base their analyses on variations in nucleic acid arrays rather than skin colour, hair texture, morphology, blood groups, and languages. Their themes tend to diversity and shared connections, not the older absolutist styles of taxonomy, category, or breed. Their studies often are oriented toward the deep past, especially the prehistory of human origins and migrations, or toward contemporary biomedical opportunities, shifting away from research that might consolidate racial regimes useful in population management and state orders.